ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETIMPANGAN PENDAPATAN DI INDONESIA - Katon Prasetyo Wibowo; Pangestuty, Farah Wulandari (Journal of Development Economic and Social Studies, 2023)
One of the recurring issues in developing countries like Indonesia is the high level of income inequality. This can be attributed to several factors, including uneven economic growth (Gross Regional Domestic Product - GRDP) among the regions in Indonesia, where some provinces experience significant development while others with low GRDP lag behind due to a lack of interest from external parties, apart from the government, to invest in these underdeveloped areas. Additionally, the low attractiveness of certain provinces to investors results in reduced labor productivity, as there is limited capital available to produce goods and services, leading to income disparities among the provinces. Therefore, one of the policies that each regional government should implement is gradually increasing the minimum wage to promote more equitable income distribution. This research aims to investigate the influence of GRDP, provincial minimum wage, labor productivity, and investment on the open unemployment rate in Indonesia from 2015 to 2019. The research utilizes a quantitative approach with secondary data in the form of a panel dataset from 34 provinces in Indonesia during the period of 2015-2019. The data is then analyzed using panel regression through Eviews version 10. The results of this research indicate that these factors significantly and jointly affect income inequality in Indonesia from 2015 to 2019.